Collusion in Quality-Segmented Markets - Iwan Bos; Marco A. Marini (Fondazione Eni Enrico Mattei (FEEM), 2020)
We appreciate the comments of and discussions with David Collie, Luis Corchón, Jean Gabszewicz, Andrey Minaev, Riccardo Saulle, Attila Tasnádi, Jacques-François Thisse and participants at the Oligo Workshop in Nottingham. All opinions and errors are ours alone.
Keywords: D4; L1; 330; Partial Cartels; Price Collusion; Market Segmentation; Vertical Dierentiation